City, state constitutionalism and the megacity - Hirschl, Ran (Oxford University Press, 2020)
More than half the world's population lives in cities; by 2050, it will be more than 75%. Cities are often the economic, cultural, and political drivers of states, and of globalization more generally. Yet, constitutionally-speaking, there has been little to no consideration of cities (and especially megacities, with populations exceeding those of many of the world's countries) as discrete or distinct constitutional or federal entities, with political identities and economic needs that often differ from rural regions or so-called "hinterlands." This book intends to taxonomize the constitutional relationship between states and (mega)cities and theorize a way forward for considering the role of the city in future. In six chapters and a conclusion, the book considers the reason for this "constitutional blind spot," the relationship between cities and hinterlands (the center/periphery divide), constitutional mechanisms for dealing with regional differences, a comparative constitutional analysis of urban-center autonomy, and recent and future innovations in city governance"--